“Do Tecnosolucionismo ao Tecnovigilantismo”: um estudo sociológico sobre os usos de emergentes tecnologias pelas forças de segurança do Ceará - Ribeiro, Marcelo da Silva (2024)
The present thesis aims primarily to sociologically analyse the social and political arrangements surrounding the recent adoption of new technological apparatuses for capturing, recording, storing, encoding, and analytically visualising images and digital data by state public security forces in Ceará. Currently in Brazil, the use of new technologies for police operations and criminal investigations is receiving greater attention within the institutional field of public security. Over the past five years, the state of Ceará has gained relative prominence on the national scene as one of the states in the country that invests most in the adoption of new electronic and digital equipment, such as state-of-the-art surveillance cameras, facial recognition technologies (FRT), and digital Big Data platforms, to assist in the state's fight against crime. Most of these “tools” have been designed and developed within the state through institutional partnerships between the government and research centres in the field of “data science.” These partnerships are one of the constitutive elements of what I methodologically refer to as the technological update movement of public security in Ceará, which is the object of study of the research that underpins this thesis. Through qualitative investigation that included documentary and bibliographic research, as well as a survey of journalistic articles and non-automated monitoring of digital content, this study involved direct observations stemming from a multisituated fieldwork and interviews with social actors directly or indirectly involved in the development and/or operationalisation of these technologies. In this way, the aim is to understand the social and political meanings and implications of the use of emerging technologies for capturing, recording, encoding, cross-referencing, and analysing images and digital data by the state public security forces of Ceará, with a particular focus on the temporal framework pertaining to the administrations of former governor Camilo Santana (PT) from 2015 to 2022. The use of these technologies reveals a complex network of heterogeneous associations that mobilise technical instruments, political actions, government initiatives, bureaucratic apparatuses, and public agents.